Rücktitelbild: Visible‐Light‐Induced N‐Heterocyclic Carbene‐Catalyzed Single Electron Reduction of Mono‐Fluoroarenes (Angew. Chem. 12/2023). (9th February 2023) - Sheng, He; Liu, Qiang; Zhang, Bei‐Bei; Wang, Zhi‐Xiang; Chen, Xiang‐Yu
Abstract : The photoreduction of monofluoroarenes is a challenge due to their high reduction potentials. In their Communication (e202218468), Zhi‐Xiang Wang, Xiang‐Yu Chen, and co‐workers show that an N‐heterocyclic carbene (NHC) and t BuOK give a photoactive charge transfer complex that generates a highly reducing NHC radical anion, enabling the single‐electron reduction of monofluoroarenes.